Temporal evolution of the plasma density cavity caused by inhomogeneous stochastic electric fields - Azarenkov, N.A.; Chibisov, D.V.; Chibisov, O.D. (Problems of Atomic Science and Technology, 2023)
The time evolution of the formation of a plasma density cavity caused by inhomogeneous stochastic electric fields is investigated. The Fokker-Planck equation, which governs the temporal evolution of the plasma electron density due to localized stochastic inhomogeneous electric fields in the frequency range of lower hybrid oscillations, is solved numerically. The spatial dependence of the plasma electron density for various times is obtained. Досліджено часову еволюцію утворення плазмової порожнини, спричиненої неоднорідними стохастичними електричними полями. Рівняння Фоккера-Планка, яке визначає часову еволюцію електронної густини плазми, що викликана локалізованими стохастичними неоднорідними електричними полями в діапазоні частот нижньогібридних коливань, розв’язано чисельно. Отримано просторову залежність густини електронів плазми для різних значень часу.